San Francisco Municipal Reports 887 (1875) - (:unkn) unknown (My University, 1872)
Prohibited the carry or discharge of firearms within Golden Gate and Buena Vista park.
Keywords: CARRY - CERTAIN PUBLIC PLACES; DISCHARGE